Should posterior cerebral artery occlusions be recanalized? Insights from the Trevo Registry - Clarençon, F; Baronnet, F; Shotar, E; Degos, V; Rolla-Bigliani, C; Bartolini, B; Veznedaroglu, E; Budzik, R; English, J; Baxter, B; Liebeskind, D S; Krajina, A; et al. (European journal of neurology, 2020)
BACKGROUND AND PURPOSE: The purpose of this study was to evaluate the safety and effectiveness of mechanical thrombectomy (MT) in patients with acute ischaemic stroke related to isolated and primary posterior cerebral artery (PCA) occlusions amongst the patients enrolled in the multicentre post-market Trevo Registry. METHOD: Amongst the 2008 patients enrolled in the Trevo Registry with acute ischaemic stroke due to large vessel occlusion treated by MT, 22 patients (1.1%) [10 females (45.5%), mean age 66.2 ± 14.3 years (range 28-91)] had a PCA occlusion [17 P1 (77.3%) and five P2 occlusions (22.7%)]. Recanalization after the first Trevo (Stryker, Fremont, CA, USA) pass and at the end of the procedure was rated using the modified Thrombolysis in Cerebral Infarction (mTICI) score. Procedure-related complications (i.e. groin puncture complication, perforation, symptomatic haemorrhage, embolus in a new territory) were also recorded. The modified Rankin Scale at 90 days was assessed. RESULTS: Median National Institutes of Health Stroke Scale at admission was 14 (interquartile range 8-16). Stroke aetiology was cardio-embolic in 68.2% of cases. Half of the patients (11/22) received intravenous tissue plasminogen activator. 54.5% of the patients were treated under general anaesthesia. Reperfusion (i.e. mTICI 2b or 3) after first pass was obtained in 65% of cases. Final mTICI 2b-3 reperfusion was obtained in all cases. Only one (4.5%) procedure-related complication was recorded (puncture site) that resolved after surgery. At 90-day follow-up, modified Rankin Scale 0-2 was obtained in 59% of the patients and 9.1% died within the first 3 months after MT. CONCLUSION: Mechanical thrombectomy for PCA occlusions seems to be safe (<5% procedure-related complications) and effective. Larger repository datasets are needed.
Keywords: arteria cerebri posterior; dospělí; Female; Tissue Plasminogen Activator; Adult; výsledek terapie; ženské pohlaví; cévní mozková příhoda; Registries; trombektomie; Internationality; lidé; katetrizace; Stroke; internacionalita; Treatment Outcome; Aged, 80 and over; ischemie mozku; retrospektivní studie; Posterior Cerebral Artery; Male; Aged; Stents; Thrombectomy; Arterial Occlusive Diseases; Brain Ischemia; Catheterization; lidé středního věku; registrace; senioři nad 80 let; tkáňový aktivátor plazminogenu; senioři; mužské pohlaví; arteriální okluzní nemoci; Retrospective Studies; Middle Aged; stenty; Humans